Entrepreneurship-technopreneurship education for undergraduates: practicality vs curriculum / Sariwati Mohd Shariff, Rohana Ngah and Saridan Abu Bakar - Mohd Shariff, Sariwati; Ngah, Rohana; Abu Bakar, Saridan (Malaysian Academy of SME & Entrepreneurship Development (MASMED), 2012)
This literary paper attempts to provide an overview on the entrepreneurship and technopreneurship education offered in the science and technology and business management programs in a public institution of higher education. These two courses are offered across faculties, academic programs, and in various parts of the duration of the academic programs. The objectives of this paper are firstly, to understand the scope and relevance of entre/technopreneurship education; secondly to identify the objectives, practicality and effectiveness of these courses. The implications of this study are to gain an understanding on the realities of conducting this education, to identify the attainment level of entrepreneurship learning outcomes and to find out the extent of entrepreneurial softskills development among the undergraduates as required in the new outcome-based education curricular design imposed by the Ministry of Higher Education. This paper suggests for a comprehensive practical instructional delivery techniques and teaching-learning in entrepreneurship-technopreneurship education so as to meet the national and educational aspirations to produce enterprising entrepreneurs and technopreneurs among graduate, and academic staff, and generation of more new innovative businesses towards. Last but not least, the noble intention towards human capital development and high-income economy are at least materialized.